Basic Concepts And Characteristics Of Professions - Prastiti, Zakya Nesa; Chadhavi, Rahmadani Aulia; Gusmiarti , Arlinsi Fatma; Imran , Ranny Fitria (Jurnal Pendidikan Rafflesia, 2025)
This article aims to define and comprehensively describe the ethics of Early Childhood Education (PAUD) teachers as the foundation of morality and professionalism in educational practice. Given the central role of PAUD teachers as the first role models for children's character formation, the study of ethical principles is crucial. The method used in this paper is a literature review or qualitative literature study, analyzing various sources such as books, scientific journals, and professional codes of ethics for teachers (Johnson, 2018; Smith & Brown, 2021).The results and key findings indicate that PAUD teacher ethics is not limited to adherence to formal rules but encompasses a set of moral principles that guide interactions with five key stakeholders: students, parents/guardians, colleagues, the profession, and the community. These principles include genuine compassion for children, honesty and objectivity in communications with parents, a sense of camaraderie with colleagues, dedication to professional development, and social awareness within the community. Consistent implementation of the code of ethics (Anderson, 2019) is key to improving the quality of services and protecting early childhood education.